TA’ARUF DALAM KHITBAH PERSPEKTIF SYAFI’I DAN JA’FARI - Akbar, Eliyyil (Musawa Jurnal Studi Gender dan Islam, 2015)
Family problems are not unusual since parents are individuals with differences in attitude, manner, and ways  of  interaction. Problems can arise due to jealousy, economic problems, affairs, immorality, and other outside issues. Such problemss are found in newly married as well as longterm couples who have not engaged in the ta’aruf processes. Generally, Indonesian people choose the pre-marriage process, and in this case, ta’aruf are overlapped so that it becomes negative. The overlapping of ta’aruf affects self-esteem, psychological wellbeing  and morality. The attitudes of the couple therefore effects their future life, men think negatively about the  relationship and women are exploited as they are considered to be influenced by their emotions. Men think that the women are not what they want because the woman cannot keep support her own existence. The mutual relationship between men and women is used to minimize the family’s problems. This paper describes ta’aruf according to the Syafi’i and Ja’fari points of view, and considers which contributes more to ta’aruf actualization in Indonesia. Both philosophies proffer that women should dress in the khibah, that the way women dress women be appropriate to the activities of daily life, and that they may khalwat whether mahram or not. Through ta’aruf one may avoid problems that lead to zina (sexual sin).